Chemical Composition of Indoor and Outdoor PM2.5 in Three Schools in the City of Rome - Luca Tofful; Cinzia Perrino (Atmosphere, 2015)
In Italy, children spend up to 30% of their time in school institutions; for this reason, the evaluation of indoor air quality in schools constitutes a necessary step forward in the direction of child health protection. In this study, we investigated the chemical composition of PM2.5 collected simultaneously indoor and outdoor in three primary schools in Rome. Seasonal variations between winter and spring/summer were evaluated, as well as the role of the main macro-sources of PM (soil, sea, traffic, secondary inorganics and organics). During winter periods, characterized by strong atmospheric stability, the main contributors were organics and combustion products, which accounted for more than 70% of the total mass both indoor and outdoor. Spring/summer period was characterized by very low outdoor concentrations (12 μg/m3 on average) and by a more balanced contribution of organic, traffic and secondary inorganic components. Indoor, the contribution of soil-related species from re-suspension of settled dust and secondary inorganic species from outdoor photochemical reactions became significant. Given that several indoor exceedances of the international air quality standards for PM2.5 were recorded during the most polluted days, the infiltration of outdoor air, due to the inadequate construction characteristics of the buildings and the absence of automated air filtration systems, seemed to be the main causes of the high PM concentrations measured indoor.